Empirical move‐on rules to inform fishing strategies: a New England case study. Issue 3 (12th January 2013) - Dunn, Daniel C; Boustany, Andre M; Roberts, Jason J; Brazer, Eric; Sanderson, Melissa; Gardner, Beth; Halpin, Patrick N
Abstract Increasingly, fisheries are being managed under catch quotas that are often further allocated to specific permit holders or sectors. At the same time, serious consideration is being given to the effects of discards on the health of target and non‐target species. Some quota systems have incorporated discard reduction as an objective by counting discards (including unmarketable fish) against the overall quota. The potential effect of the introduction of a quota system that includes accountability for discards on the fishing strategies employed by fishermen is enormous. This is particularly true for multispecies fisheries where healthy and depleted stocks co‐exist; resulting in a trip's catch being applied to very large and very small stock quotas simultaneously. Under such a scenario, fishermen have a strong incentive to minimize (i) catch of low‐quota or 'choke' stocks, (ii) regulatory discards due to minimum size limits and (iii) catch partially consumed by predators. 'Move‐on' rules (i.e. event‐triggered, targeted, temporary closure of part of a fishery when a catch or bycatch threshold is reached) have been employed in a variety of fisheries. However, their efficacy has been limited by a lack of empirical analyses underpinning the rules. Here, we examine the utility of spatiotemporal autocorrelation analyses to inform 'move‐on' rules to assist a sector of the New England Multispecies Fishery to reduce discards and maximize profits. We find the use of empirical move‐on rules could reduce catch of juvenile and choke stocks between 27 and 33%, and depredation events between 41 and 54%.